A Pragmatic Study on the Functions of Discourse Marker You Know in Economic Magazines - Guo, Man (International Journal of Linguistics, 2023)
You know has a high frequency in English communication and it is mainly used as a discourse marker. People use it in many different contexts and occasions, and hereby it fulfills various pragmatic functions. Understanding these functions and usages can help English learners to participate better in communication by improving the expression and interpretation of the discourse between the speaker and the hearer. We have retrieved you know in authentic use from the financial magazines collected in Corpus of Contemporary American English (COCA) and analyzed the pragmatic functions of discourse marker you know based on the relevance theory. This research has identified five pragmatic functions that you know fulfills: information modification marker, turn shifting marker, attitude marker, mitigator marker and advising marker.